Help From and Help to Neighbors Among Older Adults in Europe - Seifert, Alexander; König, Ronny (Frontiers in Sociology, 2019)
Neighborhoods can be a valuable source of social support particularly for older adults. Such support can be mutual; however, the influential factors in giving and receiving are unclear. This study investigated neighborhood help among the older European population using representative data for 17 countries from the Survey of Health, Ageing, and Retirement in Europe (SHARE). The analyses were based on 104,059 observations of 39,113 respondents aged 50 years and older. In general, approximately six percent of all respondents provided recently neighborhood help, and four percent received help. Moreover, the results indicate a high degree of reciprocity in giving and receiving neighborhood help. However, the situation varied widely among age groups and countries. Our multilevel results suggest that the provision and receipt of help are driven by personal characteristics (age, sex, education, income, and retirement), health resources (subjective health, activities of daily living, and instrumental activities of daily living), living situation (homeownership, location, and length of time in a residence), social factors (marital status, partner, parents, and children), and contextual factors (gross domestic product, social expenditures, poverty rate, Gini index, population density, country-centered satisfaction with life, living, and relationships).